Vlado Kristl- Ich bin ein Mensch-Versuch - Maier, Joana Pauline; Nechleba, Markus (Germany : Weekend Production, 2006)
The film follows artist Vlado Kristl's life between 2002-2004. He was a filmmaker and artist from Zagreb, Croatia, best known for his celebrated animations and short films.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films